Engineered Pullulan–Collagen Composite Dermal Hydrogels Improve Early Cutaneous Wound Healing - Wong, Victor W. (Tissue Eng Part A, 2011)
New strategies for skin regeneration are needed to address the significant medical burden caused by cutaneous wounds and disease. In this study, pullulan–collagen composite hydrogel matrices were fabricated using a salt-induced phase inversion technique, resulting in a structured yet soft scaffold for skin engineering. Salt crystallization induced interconnected pore formation, and modification of collagen concentration permitted regulation of scaffold pore size. Hydrogel architecture recapitulated the reticular distribution of human dermal matrix while maintaining flexible properties essential for skin applications. In vitro, collagen hydrogel scaffolds retained their open porous architecture and viably sustained human fibroblasts and murine mesenchymal stem cells and endothelial cells. In vivo, hydrogel-treated murine excisional wounds demonstrated improved wound closure, which was associated with increased recruitment of stromal cells and formation of vascularized granulation tissue. In conclusion, salt-induced phase inversion techniques can be used to create modifiable pullulan–collagen composite dermal scaffolds that augment early wound healing. These novel biomatrices can potentially serve as a structured delivery template for cells and biomolecules in regenerative skin applications.